AN EXCEPTIONAL SAGE AND THE NEED FOR THE MESSENGER: THE POLITICS OF FIṬRA IN A 12TH-CENTURY TALE. Issue 2 (September 2019) - von Doetinchem de Rande, Raissa A.
Abstract: This paper argues that Ibn Ṭufayl (d. 1185) in his Ḥayy ibn Yaqẓān offers a surprisingly intellectual reading of the term fiṭra (pl. fiṭar ) and one that has significant consequences for our understanding of the story. We will see that at crucial junctures in the text, fiṭra emerges solely in an intellectual context, implying a gulf amongst humanity that defies common understandings of the term as egalitarian. This gulf, I argue, illuminates the political implications of the tale. For while he emphasizes the broad compatibility of the more established, revealed and the philosophical path recently arrived in Andalusia, Ibn Ṭufayl, with the help of fiṭra, shows that the philosophical life is one for the very few. Attention to Ibn Ṭufayl's use of fiṭra might thus explain one of his reasons for writing this tale for the court. Its overall message heightens the role of religion and tempers the political significance of philosophy in two ways: by arguing that only select individuals have the capacity to access truth independently from revelation; and by denying these exceptionally gifted the ability to communicate their findings to the masses. Résumé: Cet article part d'une lecture inhabituelle, inégalitaire, du terme fiṭra (pl. fiṭar ) dans le Ḥayy ibn Yaqẓān d'Ibn Ṭufayl (d. 1185) ; cette lecture modifie de façon conséquente notre compréhension de l'ensemble de l'œuvre. Nous verrons qu'à des moments cruciaux de la démonstration, il n'utilise le terme fiṭra que pour décrire la capacité des êtres à raisonner, ce qui implique qu'un fossé divise l'humanité et défie les acceptions ordinairement égalitaires de la fiṭra . Ce fossé éclaire, selon moi, les implications politiques du conte. Alors qu'Ibn Ṭufayl insiste sur la compatibilité entre la philosophie récemment parvenue en Andalousie et celle, plus établie, de la religion révélée, il montre, à l'aide de la fiṭra, que la vie philosophique n'est destinée qu'à un petit nombre. Prêter attention à l'usage qu'Ibn Ṭufayl fait de la fiṭra peut aider à expliquer l'une des raisons pour lesquelles il écrivit ce conte pour la cour. Son message global accentue le rôle de la religion et tempère l'importance politique de la philosophie de deux façons : d'une part, en avançant que seuls quelques individus choisis sont capables d'accéder à la vérité indépendamment de la révélation ; d'autre part, en refusant à ces êtres exceptionnellement doués la capacité de communiquer leurs découvertes aux masses.